Delayed Diagnosis of Tuberculoma in a Child with Nephritis due to Systemic Lupus Erythematosus - Nataprawira, Heda Melinda (Turk Thorac J, 2018)
Tuberculoma is one of the manifestations of tuberculosis infection in the central nervous system. Even though its prevalence is only 1%, the mortality rate is high. Clinical presentation in immunocompromised patients with tuberculoma maybe different, thus making the diagnosis difficult. We present the case of a 13-year-old girl who was admitted for routine intravenous administration of cyclophosphamide and steroid therapy for nephritis due to systemic lupus erythematosus. She experienced severe headache and focal seizure on the second day of hospitalization. Neurology examination did not show any abnormalities. The Xpert MTB/RIF from the cerebrospinal fluid and sputum yielded negative results. Computed tomography scan and magnetic resonance imaging showed tuberculoma with caseous necrosisaround the fibrous capsule in the right occipital lobe of the brain. Electroencephalography showed no abnormalities. Clinical improvement was seen after 3weeks of treatment; however, antituberculosis drug-induced hepatotoxicity occurred.